2007
DOI: 10.1109/tsp.2007.901138
|View full text |Cite
|
Sign up to set email alerts
|

Complex Noise Analysis of DMT

Abstract: In this paper, we consider discrete multitone (DMT) or baseband orthogonal frequency-division multiplexing (OFDM) modulation and perform a detailed noise analysis which takes into account dependencies and power (variance) differences of real and imaginary part after the complex-valued discrete Fourier transform (DFT). The derivation is based on the so-called pseudocovariance matrix of a complex random vector, which was introduced by Neeser and Massey (1993). We show that the relevant pseudocovariance matrix is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Whereas in many real-world scenarios the noise vector happens to be circular, so that the results of Section 5.1 apply, there are also practically relevant scenarios, where the noise vector is known to be improper. More specifically, DMT modulation, which is widely used in xDSL applications [18], yields an equivalent system channel that exactly matches the situation considered here [8,9]. We also note that capacity results for improper Gaussian distributed noise vectors could be alternatively derived by making use of an equivalent real-valued channel of dimension 2n × 2m that is obtained by appropriate stacking of real and imaginary parts.…”
Section: Deterministic Channel Matrix and Improper Gaussian Noise Vectormentioning
confidence: 59%
See 1 more Smart Citation
“…Whereas in many real-world scenarios the noise vector happens to be circular, so that the results of Section 5.1 apply, there are also practically relevant scenarios, where the noise vector is known to be improper. More specifically, DMT modulation, which is widely used in xDSL applications [18], yields an equivalent system channel that exactly matches the situation considered here [8,9]. We also note that capacity results for improper Gaussian distributed noise vectors could be alternatively derived by making use of an equivalent real-valued channel of dimension 2n × 2m that is obtained by appropriate stacking of real and imaginary parts.…”
Section: Deterministic Channel Matrix and Improper Gaussian Noise Vectormentioning
confidence: 59%
“…In recent research-for an comprehensive overview see [3]-it has been shown that exploiting circularity/properness of complex-valued signals or lack of it (non-circularity/improperness) is able to significantly enhance the performance of the applied signal processing techniques. More specifically, for the field of communications, it has been observed that important digital modulation schemes including binary phase shift keying (BPSK), pulse amplitude modulation (PAM), Gaussian minimum shift keying (GMSK), offset quaternary phase shift keying (OQPSK), and baseband (but not passband) orthogonal frequency division multiplexing (OFDM), which is commonly called discrete multitone (DMT), (potentially) produce non-circular/improper complex baseband signals, see e.g., [4][5][6][7][8][9]. Non-circular/improper baseband communication signals can also arise due to imbalance between their in-phase and quadrature (I/Q) components, and several techniques for compensating for I/Q imbalance have been proposed [10][11][12].Information theory, on the other hand, addresses fundamental performance limits of communication systems and also has large impact on many other scientific areas, where stochastic models are used.…”
mentioning
confidence: 99%
“…Power Systems Modulation DoA Estimation [7], [32], [159] Multiple Access Coding Radio Communications [5], [28] Communications BPSK/PAM [4], [5], [22] GMSK OQPSK [23]- [25] Baseband OFDM [27] Transceiver Impairments [ Rotationally Variant Channel [6] Feature Extraction Improved Estimation Biomedical Engineering [102] Medicine ECG [145] EEG [147] EOG [147] fMRI [6], [20], [21] , [124], [146] SSB/VSB [26] DS-CDMA [45] STBC [28] Analysis Treatment Squeezed States of Light [153] Biphoton States in Q-OCT [154] Anisotropic Noise Imbalanced Data Channels Reflections…”
Section: Three Phase Systemsmentioning
confidence: 99%
“…Similarly, Subramaniam et al introduce asymmetry in 8-PSK to increase the minimum product distance reducing error events in TCM [268]. For colored noise compensation, Taubock prefers optimally rotated rectangular symbol constellations over common quadratic QAM in order to minimize capacity loss and SEP [27].…”
Section: A Asymmetric Signal Designmentioning
confidence: 99%
See 1 more Smart Citation